Effect of long-term temperature stress on the intestinal microbiome of an invasive snail - Li, Shuxian; Qian, Zijin; Gao, Shuo; Shen, Wenjia; Li, Xuexia; Li, Hong; Chen, Lian (Frontiers in Microbiology, 2022)
The gut microbiome is vital to the physiological and biochemical functions of the host, and changes in the composition of these microbial communities may affect growth and adaptability to the environment. Pomacea canaliculata is an invasive freshwater snail which has become a serious agricultural pest. Temperature adaptation is considered an important reason for the widespread distribution of this species. To date, the contribution of the gut microbes to host fitness of P. canaliculata during long-term temperature stress is not well understood. In this study, the morphological changes and intestinal microbiome of P. canaliculata under long-term stress at low temperature (15℃) and high temperature (35℃) were investigated with laboratory experiments. Compared with control group (25℃), the alpha diversity increased and pathogenic bacteria enriched changed under high and low temperature stress. The effect of high temperature stress on the intestinal microbiome of P. canaliculata was more significant than that of low temperature stress. A sustained high temperature environment led to an increase in the abundance of pathogenic bacteria, such as Aeromonas and Enterobacter, and a decrease in the abundance of immune-related bacteria such as Bacteroidetes, Firmicutes, and Lactococcus. These intestine microbiome changes can increase the risk of diseases like intestinal inflammation, and lead to more deaths at high temperature environments. In addition, with the extension of stress time from 14d to 28 d, the beneficial bacteria such as Bacteroidetes, Firmicutes, and Lactococcus were significantly enriched, while potential pathogenic bacteria such as Pseudomonas, Acinetobacter, Shivalella, and Flavobacterium decreased, suggesting that intestinal microbiota may play an important role in host response to heat stress. These results are consistent with previously reported results that the survival rate of both male and female P. canaliculata no longer significantly reduced after 21 d of high temperature stress, suggesting that the surviving P. canaliculata had gradually adapted to high temperature environments under long-term high temperature stress.